Conductive polyether ester fiber foot pressure sensor, foot pressure insole and preparation method thereof
The foot pressure sensor of conductive polyetherester fibers was prepared by electrospinning, which solved the accuracy and repeatability of the existing foot pressure measurement methods, and achieved high sensitivity and stability foot pressure monitoring effect.
Patent Information
- Application Number
- CN202510250213.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The existing foot pressure measurement methods have problems such as low accuracy, poor repeatability, poor comfort and high cost, and require frequent calibration, which affects long-term use.
Polyetherester fiber membranes were prepared by electrospinning, soaked in an alcohol solution containing pyrrole and tanninic acid, and then soaked in a ferric chloride solution to prepare a foot pressure sensor for conductive polyetherester fibers.
It has achieved a foot pressure sensor with high sensitivity, good stability and good biocompatible, and can maintain stable detection performance after long-term use. It is suitable for daily walking, exercise rehabilitation and medical monitoring.
Smart Images

Figure CN119736794A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a foot pressure sensor of conductive polyether ester fiber, a foot pressure insole and a preparation method thereof, belonging to the technical field of footwear parts. Background Art
[0002] The foot is the only part of the human body that comes into contact with the ground during normal human activities, and has an important impact on personal health, especially for the elderly, athletes, and individuals with certain diseases. Abnormal changes in foot pressure may lead to a series of health problems, such as lower limb deformities, sports injuries, plantar pain, etc. At present, the existing foot pressure measurement method mainly consists of a traditional foot pressure plate with a thin film pressure sensor, which has problems such as low accuracy, poor repeatability, poor comfort, and high cost. In addition, it needs to be calibrated before each use, which seriously affects its long-term use in daily life.
[0003] Polyetherester has many advantages such as excellent heat resistance, flexural fatigue resistance, wear resistance, high strength and toughness, and easy processing and molding. These characteristics make it an ideal carrier material for foot pressure insole sensors. First of all, polyetherester fiber has excellent elasticity, which enables the sensor made of it to maintain a good shape and have high sensitivity at the same time. Secondly, polyetherester fiber has high durability and breathability, which makes it comfortable and stable as a wearable device. However, since polyetherester is a traditional polymer and is not conductive, it is necessary to modify the polyetherester fiber. It is also challenging to achieve the modification of polyetherester fiber and the preparation of foot pressure monitoring sensors in a low-cost, mass-producible, and highly stable manner. Summary of the invention
[0004] The present invention provides a foot pressure sensor of conductive polyetherester fiber, a foot pressure insole and a preparation method thereof, which can effectively solve the above problems.
[0005] The present invention is achieved in that: A method for preparing a foot pressure sensor of conductive polyetherester fiber comprises the following steps: S1, preparation of polyetherester fiber membrane by electrospinning; S2, soaking the polyetherester fiber membrane in an alcohol solution containing pyrrole and tannic acid for a period of time; the alcohol in the alcohol solution containing pyrrole and tannic acid is 40-60% alcohol, wherein the concentration of pyrrole is 10-15v / v%, and the concentration of tannic acid is 2-12wt%; S3, soaking the polyetherester fiber membrane in a ferric chloride solution for a period of time to obtain a conductive polyetherester fiber foot pressure sensor. In some embodiments, the solvent of the electrospinning solution is hexafluoroisopropanol; and the concentration of the spinning solution is 4-6wt%.
[0006] In some embodiments, the electrospinning parameters are: voltage 25-30 kV, flow rate 15-25 μL / min, roller speed 280-320 rpm, humidity 40-50%, and spinning time 3.5-4.5 h.
[0007] In some embodiments, the concentration of the ferric chloride solution is 5-10 wt %.
[0008] In some embodiments, the soaking time of step S2 is 50-70 min and the temperature is 3.5-4.5°C.
[0009] In some embodiments, the soaking time of step S3 is 22-26 hours and the temperature is 3.5-4.5°C.
[0010] A foot pressure sensor made of conductive polyetherester fiber prepared by the method.
[0011] A foot pressure insole comprises the foot pressure sensor made of conductive polyetherester fiber.
[0012] A method for preparing a foot pressure insole comprises the following steps: (1) First, a layer of patterned electrodes is plated on the polyimide substrate by spraying, and then the polyimide with the electrode is placed in a constant temperature drying oven for curing; (2) fixing the foot pressure sensor of the conductive polyetherester fiber on the patterned electrode by glue; (3) Finally, place the polyimide encapsulation layer on the top for encapsulation.
[0013] In some embodiments, the electrode is made of conductive silver paste.
[0014] The beneficial effects of the present invention are: The present invention obtains a conductive polyetherester fiber sensor by modifying polyetherester. The foot pressure monitoring insole assembled with the conductive polyetherester fiber sensor has many advantages such as high sensitivity, good stability, good biocompatibility, portability and ease of use. It can maintain stable detection performance after long-term use and is suitable for different environments such as daily walking, sports rehabilitation and medical monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is a flow chart for the preparation of polyetherester fiber.
[0017] Figure 2 The preparation flow chart of conductive polyetherester fiber.
[0018] Figure 3 The schematic diagram of the foot pressure monitoring insole structure assembled based on the conductive polyether ester fiber sensor. Among them, 1-polyimide substrate, 2-conductive silver electrode, 3-conductive polyether ester fiber sensor, 4-polyimide packaging layer.
[0019] Figure 4 Elongation at break and electrical conductivity of polyetherester fibers with different pyrrole contents.
[0020] Figure 5 The scanning electron microscope images of polyetherester fibers include: (a) polyetherester, (b) polypyrrole / polyetherester, (c) tannic acid 0.25 / polypyrrole / polyetherester, (d) tannic acid 0.5 / polypyrrole / polyetherester, and (e) tannic acid 1 / polypyrrole / polyetherester.
[0021] Figure 6 The mechanical properties of polyetherester-based fibers are shown in Figure 2. (a) Stress-strain curve of polyetherester-based fibers and (b) Stress-strain curve of polyetherester fibers with different tannic acid contents.
[0022] Figure 7 is the electrical conductivity of polyetherester fibers with different tannic acid contents.
[0023] Figure 8 Sensing performance of tannic acid / polypyrrole / polyetherester fiber. (a) Finger bending, (b) wrist bending, (c) elbow bending. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The embodiment of the present invention provides a method for preparing a foot pressure sensor of conductive polyetherester fiber, comprising the following steps: S1, preparation of polyetherester fiber membrane by electrospinning; S2, soaking the polyetherester fiber membrane in an alcohol solution containing pyrrole and tannic acid for a period of time; the alcohol in the alcohol solution containing pyrrole and tannic acid is 40-60% alcohol, wherein the concentration of pyrrole is 10-15v / v%, and the concentration of tannic acid is 2-12wt%; S3, soaking the polyetherester fiber membrane in a ferric chloride solution for a period of time to obtain a conductive polyetherester fiber foot pressure sensor. The embodiment of the present invention prepares polyetherester fiber by an electrostatic spinning method, first immersing the polyetherester fiber in a 50% alcohol solution, and then immersing it in a ferric chloride solution. Pyrrole monomer and ferric chloride can be polymerized in situ to generate conductive black polypyrrole, which is a rigid material and will destroy the flexibility of polyetherester fiber. Since there are a large number of active groups on the surface of tannic acid, a cross-linked network structure can be formed with the polyetherester molecular chain, so the flexibility of the polyetherester fiber can be maintained to a certain extent. The conductive polyetherester fiber successfully prepared by this method can have both good mechanical properties and excellent conductivity.
[0026] After adding tannic acid, more uniform spore-like polypyrrole is deposited on the fiber surface. Since tannic acid is an active substance, it can improve the interfacial bonding force between polyetherester fiber membrane and polypyrrole, which is conducive to the formation of a more uniform polypyrrole coating. With the increase of tannic acid content, the increase of fiber elongation at break is not obvious, but the conductivity of the fiber decreases significantly with the increase of tannic acid content. This is because tannic acid molecules contain a large number of polar groups, which can interact with polypyrrole molecular chains to produce a toughening effect, and the phenolic hydroxyl groups in tannic acid molecules can form a cross-linked network structure with polypyrrole molecular chains. When the material is subjected to external force, this cross-linked network can absorb more energy, thereby increasing the elongation at break of the material. In addition, tannic acid can also react with ferric chloride. When the tannic acid content is too high, on the one hand, it will consume part of the ferric chloride, thereby affecting the degree of polymerization of polypyrrole; on the other hand, tannic acid carries a negative charge, which will neutralize the positive charge on the polypyrrole chain, resulting in a decrease in the concentration of carriers, thereby reducing the conductivity. Preferably, when the tannic acid content is 2.75%, the conductivity and elongation at break of the tannic acid / polypyrrole / polyetherester fiber membrane can be balanced, which is beneficial to subsequent sensing performance testing.
[0027] In some embodiments, the solvent of the electrospinning solution is hexafluoroisopropanol, and the concentration of the spinning solution is 4-6wt%, which can ensure the stability of the spinning process and the quality of the final fiber product.
[0028] In some specific implementation cases, the parameters used for electrospinning are set as follows: the applied voltage range is controlled between 25 and 30 kilovolts to ensure the suitability of the electric field strength; the flow rate of the solution is precisely adjusted to 15 to 25 microliters per minute to ensure the continuity and stability of fiber formation; the speed of the roller is set at 280 to 320 revolutions per minute to maintain the uniformity of fiber deposition; the ambient humidity is strictly controlled between 40% and 50% to reduce electrostatic interference and optimize fiber quality; the entire spinning process lasts for 3.5 to 4.5 hours to ensure sufficient deposition and solidification of the fiber. Under these optimized parameter conditions, it can be clearly observed that there is no beading phenomenon during the spinning process, the fiber morphology is uniform and consistent, and it shows extremely excellent spinnability, thus providing a reliable guarantee for the preparation of high-quality fiber materials.
[0029] In some specific embodiments, the concentration range of the ferric chloride solution is set to 5% to 10% by weight (wt%) to ensure that the solution can exert the best chemical reaction effect during the treatment process. The selection of this concentration is based on multiple experimental verifications to achieve a predetermined treatment effect and reaction efficiency.
[0030] In some specific embodiments, the immersion time of step S2 is precisely controlled between 50 minutes and 70 minutes, and the immersion temperature is strictly maintained in the range of 3.5 degrees Celsius to 4.5 degrees Celsius. Such a combination of time and temperature is to ensure that the material can fully react with the solution during the immersion process, thereby achieving the expected treatment effect and avoiding incomplete reaction due to too short a time or inappropriate temperature.
[0031] In some detailed embodiments, the soaking time of step S3 is set to 22 hours to 26 hours, and the soaking temperature is also controlled within the range of 3.5 degrees Celsius to 4.5 degrees Celsius. This long soaking period and precise temperature control are to ensure that the material can undergo sufficient chemical changes in this step to achieve the final treatment goal and ensure the stability and reliability of the entire process.
[0032] The embodiment of the present invention provides a foot pressure sensor composed of conductive polyetherester fiber prepared by a specific method. The sensor utilizes the unique properties of conductive polyetherester fiber to accurately sense and transmit foot pressure information. In addition, the embodiment of the present invention also provides a new type of foot pressure insole, the core component of which is the conductive polyetherester fiber foot pressure sensor described above. By assembling multiple conductive polyetherester fiber sensors according to a specific layout, a foot pressure insole that can fully cover the sole of the foot is formed. Furthermore, advanced deep learning technology is used to perform intelligent analysis on the collected foot pressure data, thereby achieving accurate detection of lower limb deformities.
[0033] In the field of lower limb deformity detection, existing technical means often rely on traditional imaging examination methods, such as X-rays, CT scans, etc., or detection methods that rely on manual analysis by professional doctors. These traditional methods not only need to rely on the experience and judgment of professional doctors, but also the diagnosis process is relatively cumbersome and time-consuming, and it is difficult to meet the needs of real-time monitoring and automated diagnosis. In addition, the high detection cost also limits its wide application in daily health management. Therefore, how to develop an efficient, low-cost and automated detection foot pressure sensor to achieve early detection and timely intervention of lower limb deformities has become an important technical problem that needs to be solved urgently. The present invention is proposed to fill this technical gap and provide a new solution.
[0034] The embodiment of the present invention provides a method for preparing a foot pressure insole, which specifically includes the following steps: First, on the polyimide base material, a layer of electrode layer with a specific pattern is evenly plated by means of glue dispensing and spraying technology. After the electrode layer is plated, the polyimide base on which the electrode has been plated is placed in a constant temperature drying oven and cured for a certain period of time to ensure that the electrode layer is tightly combined with the base material and enhance its stability and durability. Next, the pre-prepared foot pressure sensor made of conductive polyether ester fiber material is firmly fixed on the cured patterned electrode by applying an appropriate amount of glue to ensure good conductivity between the sensor and the electrode and stable signal transmission. In the last step, a layer of polyimide packaging material is covered on the top layer, and an overall packaging process is performed to protect the internal electrodes and sensors and prevent interference from external environmental factors.
[0035] In some specific embodiments, the electrode material is a silver paste material with excellent conductivity to further improve the conductivity of the electrode and the sensing accuracy of the overall insole.
[0036] Example 1 Preparation of polyetherester fiber by electrospinning: like Figure 1 As shown in the figure, 0.798 g of polyether ester particles were added to 10 mL of hexafluoroisopropanol (HFIP), and the polyether ester particles were stirred continuously at room temperature until they were completely dissolved, thereby preparing a polyether ester spinning solution with a concentration of 5 wt%. The spinning solution was electrospun for 4 hours at a voltage of 25 kV, a flow rate of 20 µL / min, and a roller speed of 300 rpm, and polyether ester fibers were successfully collected on the roller.
[0037] Example 2 Preparation of conductive polyetherester fiber: As shown in Example 1, polyetherester fibers were prepared by electrospinning.
[0038] The preparation process of conductive polyetherester fiber is as follows: First, 0.3 mL and 1.2 mL of pyrrole monomer were added to 50% ethanol solution, respectively, to prepare 10 mL of pyrrole / 50% ethanol solution, and stored at 4°C. Next, an 8% ferric chloride solution was prepared and also stored in a refrigerator at 4°C. Subsequently, the polyetherester fiber membrane was immersed in pyrrole / 50% ethanol solution with different pyrrole contents at 4°C for 1 hour, and then immersed in 8% ferric chloride solution, and continued to be immersed at 4°C for 24 hours. The fiber samples were named polypyrrole X / polyetherester (where x represents the volume of the added pyrrole monomer).
[0039] The mechanical properties were measured at room temperature using a micro tensile tester (TST 250V, Linkam, UK). The sample to be tested was cut into a dumbbell shape, and the elongation at break of the sample was tested using a 20N sensor at a tensile rate of 50μm / min. The conductivity of the TPEE-PPY-TAX fiber was measured using a four-probe tester (RTS-9, Guangzhou Four Probe Technology Co., Ltd.). The sample fiber membrane was placed directly under the four-probe, the knob was adjusted so that the probe contacted the sample surface, and the test button was clicked to test the sample.
[0040] After comparative analysis, the optimal pyrrole content was selected. Figure 4 shown.
[0041] Example 3 Preparation of conductive polyetherester fiber: As shown in Example 1, electrospun polyetherester fibers were prepared.
[0042] The preparation process of conductive polyetherester fiber is as follows: First, prepare tannic acid / polypyrrole / 50% alcohol solution. Dissolve 1.2 mL of pyrrole monomer in 8.8 mL of 50% ethanol solution, then add 0 g, 0.25 g, 0.5 g and 1 g of tannic acid respectively, and store them in a refrigerator at 4 °C after they are completely dissolved. At this time, the concentrations of tannic acid are 0, 2.75%, 5.51% and 11.01%, respectively. Next, prepare 8% ferric chloride solution, which is also stored in a refrigerator at 4 °C.
[0043] The polyetherester fiber membrane was immersed in tannic acid / polypyrrole / 50% alcohol solutions with different tannic acid contents at 4 °C for 1 hour. Subsequently, the polyetherester fiber membrane was immersed in 8% ferric chloride solution at 4 °C for 24 hours. The excess polypyrrole was rinsed off with deionized water and dried at 60 °C for 1 hour to finally obtain tannic acid / polypyrrole / polyetherester fiber. The fiber samples were named tannic acid X / polypyrrole / polyetherester (where X represents the mass of added tannic acid).
[0044] The optimal amount of tannic acid added was determined through experiments, and the tannic acid / polypyrrole / polyetherester fiber was selected as the sample for subsequent experiments.
[0045] Embodiment 4 Assembly of foot pressure monitoring insole: First, a layer of patterned electrode is plated on the polyimide substrate using a dispensing spray process, and the electrode material is a conductive silver paste. Subsequently, the polyimide with the plated electrode is placed in a constant temperature drying oven for curing, and the temperature is set to 120°C for 10 minutes. Next, the aforementioned conductive polyetherester fiber sensor is fixed to the patterned electrode with glue. Finally, the polyimide encapsulation layer is placed on the top layer and encapsulated with glue to prevent the sensor from being exposed to the air and causing performance changes. For a detailed structural diagram, see Figure 3 .
[0046] Figure 4 The comparison of elongation at break and conductivity of two conductive fibers with different pyrrole contents is shown. Figure 1 Data analysis shows that when the pyrrole content increases from 0.3 mL to 1.2 mL, the elongation at break changes slightly, while the conductivity increases significantly from 1.0417 S / cm to 2.7924 S / cm. This indicates that polypyrrole 1.2 / polyetherester fiber has better conductivity, so 1.2 mL is determined as the optimal addition amount of pyrrole monomer for subsequent experiments. In order to further improve the flexibility of conductive polyetherester fiber, different proportions of tannic acid were added to the pyrrole / 50% ethanol solution in the experiment to explore the optimal addition amount of tannic acid.
[0047] Figure 5 Scanning electron microscope images of polyetherester fibers are shown, showing that there is no beading during the spinning process, indicating that polyetherester fibers have excellent spinnability. After adding tannic acid, more uniform spore-like polypyrrole is deposited on the fiber surface. Since tannic acid is an active substance, it can enhance the interfacial bonding between the polyetherester fiber membrane and polypyrrole, helping to form a more uniform polypyrrole coating.
[0048] Figure 6 The tensile stress-strain curves of polyetherester fibers are presented. Figure 6 As can be seen from part (a) of the graph, the elongation at break of the polyetherester fiber is as high as 450%. However, when the conductive material polypyrrole is deposited on its surface, the elongation at break of the fiber drops significantly to only 40%. Tannic acid is rich in phenolic hydroxyl groups and can form a cross-linked network structure with polypyrrole molecular chains. By adding tannic acid to the pyrrole / 50% alcohol solution, the elongation at break of the prepared tannic acid / polypyrrole / polyetherester fiber can reach 380%. In order to determine the optimal amount of tannic acid added, 0 g, 0.25 g, 0.5 g and 1 g of tannic acid were added to the pyrrole / 50% alcohol solution, respectively, and the tannic acid contents in the resulting conductive fibers were 0, 2.75%, 5.51% and 11.01%, respectively. Its tensile properties are shown in Figure 2. Figure 6 As shown in (b), as the tannic acid content increases from 0.25 g to 1 g, the elongation at break of the fiber does not increase significantly, basically maintaining at around 380%, but the conductivity decreases significantly with the increase of tannic acid content, from 2.99 S / cm to 0.1 S / cm ( Figure 7). This is because tannic acid molecules contain a large number of polar groups, which interact with polypyrrole molecular chains to produce a toughening effect, and the cross-linked network structure formed by phenolic hydroxyl groups and polypyrrole molecular chains can absorb more energy when the material is subjected to external force, thereby improving the elongation at break of the material. In addition, tannic acid can react with ferric chloride. When the tannic acid content is too high, on the one hand, it will consume part of the ferric chloride and affect the degree of polymerization of polypyrrole; on the other hand, the negative charge of tannic acid will neutralize the positive charge on the polypyrrole chain, reduce the carrier concentration, and reduce the conductivity. When the tannic acid content is 2.75%, the conductivity of the tannic acid / polypyrrole / polyetherester fiber membrane is 2.99 S / cm, and the elongation at break can reach 380%, so this sample was selected for subsequent sensing performance testing.
[0049] Figure 8 The response curves in the figure are plotted by recording the resistance change (R-R0) / R0 by the source meter, where R and R0 represent the resistance of the coated sensor before and after the motion is applied. Since the composite fiber surface is covered with a polypyrrole conductive coating, the curling and release of the fingers, wrist, and elbow joints drive the stretching and recovery of the tannic acid / polypyrrole / polyetherester fiber, causing multi-scale deformation of the conductive path formed by the polypyrrole coating. Therefore, when the tannic acid / polypyrrole / polyetherester fiber undergoes repetitive motions of straightening and bending, its (R-R0) / R0 ratio fluctuates regularly. Figure 8 (a) shows that as the bending angle of the finger increases, the resistance change rate of the tannic acid / polypyrrole / polyetherester fiber also increases. The same resistance change occurs when the wrist and elbow are bent ( Figure 8 (b) and (c)).
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a foot pressure sensor of conductive polyetherester fiber, characterized in that: The following steps are involved: S1, preparation of polyetherester fiber membrane by electrospinning; S2, soaking the polyetherester fiber membrane in an alcohol solution containing pyrrole and tannic acid for a period of time; the alcohol in the alcohol solution containing pyrrole and tannic acid is 40-60% alcohol, wherein the concentration of pyrrole is 10-15v / v%, and the concentration of tannic acid is 2-12wt%; S3, soaking the polyetherester fiber membrane in a ferric chloride solution for a period of time to obtain a conductive polyetherester fiber foot pressure sensor.
2. The method for preparing a foot pressure sensor of conductive polyetherester fiber according to claim 1, characterized in that: The solvent of the electrospinning solution is hexafluoroisopropanol; the concentration of the spinning solution is 4-6wt%.
3. The method for preparing a foot pressure sensor of conductive polyetherester fiber according to claim 1, characterized in that: The electrospinning parameters were: voltage 25-30 kV, flow rate 15-25 μL / min, roller speed 280-320 rpm, humidity 40-50%, and spinning time 3.5-4.5 h.
4. The method for preparing a foot pressure sensor of conductive polyetherester fiber according to claim 1, characterized in that: The concentration of the ferric chloride solution is 5-10wt%.
5. The method for preparing a foot pressure sensor of conductive polyetherester fiber according to claim 1, characterized in that: The soaking time of step S2 is 50-70 minutes, and the temperature is 3.5-4.5°C.
6. The method for preparing a foot pressure sensor of conductive polyetherester fiber according to claim 1, characterized in that: The soaking time of step S3 is 22-26 hours, and the temperature is 3.5-4.5°C.
7. A foot pressure sensor made of conductive polyetherester fiber prepared by the method for preparing a foot pressure sensor made of conductive polyetherester fiber according to any one of claims 1 to 6.
8. A foot pressure insole, characterized in that: A foot pressure sensor comprising the conductive polyetherester fiber as claimed in claim 7.
9. A method for preparing a foot pressure insole, characterized in that: The following steps are involved: (1) First, a layer of patterned electrodes is plated on the polyimide substrate by spraying, and then the polyimide with the electrode is placed in a constant temperature drying oven for curing; (2) fixing the conductive polyetherester fiber foot pressure sensor on the patterned electrode by glue; (3) Finally, place the polyimide encapsulation layer on the top for encapsulation.
10. The method for preparing the foot pressure insole according to claim 9, characterized in that: The electrode is made of conductive silver paste.
Citation Information
Patent Citations
Electrically-conductive porous three-dimensional tissue engineering bracket material and preparation method thereof
CN109847106A
Preparation method of tannic acid cross-linked polypyrrole conductive polymer hydrogel and application thereof
CN113831556A
Spun-bonded non-woven fabric based composite fiber membrane for photo-thermal desalination and preparation method thereof
CN116145422A
Conductive silk fibroin material as well as preparation method and application thereof
CN116656137A
Fabric with antistatic performance
CN118087129A